Human Milk Fat Globule Membrane Contains Hundreds of Abundantly Expressed and Nutritionally Beneficial Proteins That Are Generally Lacking in Caprine Milk - Juvarajah, Thaneswari; Wan-Ibrahim, Wan Izlina; Ashrafzadeh, Ali; Othman, Shatrah; Hashim, Onn Haji; Fung, Shin Yee; Abdul-Rahman, Puteri Shafinaz (Mary Ann Liebert, 2018)
Background: Bioactive proteins from milk fat globule membrane (MFGM) play extensive roles in cellular processes and defense mechanisms in infants. The aims of this study were to identify differences in protein compositions in human and caprine MFGM using proteomics and evaluate possible nutritional benefits of caprine milk toward an infant's growth, as an alternative when breastfeeding or human milk administration is not possible or inadequate. Materials and Methods: Human and caprine MFGM proteins were isolated and analyzed, initially by polyacrylamide gel electrophoresis, and subsequently by quadrupole time-of-flight liquid chromatography-mass spectrometry. This was then followed by database search and gene ontology analysis. In general, this method selectively analyzed the abundantly expressed proteins in milk MFGM. Results: Human MFGM contains relatively more abundant bioactive proteins compared with caprine. While a total of 128 abundant proteins were detected in the human MFGM, only 42 were found in that of the caprine. Seven of the bioactive proteins were apparently found to coexist in both human and caprine MFGM. Results/Discussion: Among the commonly detected MFGM proteins, lactotransferrin, beta-casein, lipoprotein lipase, fatty acid synthase, and butyrophilin subfamily 1 member A1 were highly expressed in human MFGM. On the other hand, alpha-S1-casein and EGF factor 8 protein, which are also nutritionally beneficial, were found in abundance in caprine MFGM. The large number of human MFGM abundant proteins that were generally lacking in caprine appeared to mainly support human metabolic and developmental processes. Conclusion: Our data demonstrated superiority of human MFGM by having more than one hundred nutritionally beneficial and abundantly expressed proteins, which are clearly lacking in caprine MFGM. The minor similarity in the abundantly expressed bioactive proteins in caprine MFGM, which was detected further, suggests that it is still nutritionally beneficial, and therefore should be included when caprine milk-based formula is used as an alternative.